Investigating The Integration Of A Workplace English Digital Course Into The Curriculum Of The University Of Technology And Applied Sciences In Oman (Journal of Namibian Studies : History Politics Culture, 2023)
English for the workplace is considered a crucial factor across various fields, local and international. Accordingly, the training of undergraduates at technical and vocational institutes must include teaching and learning workplace English skills and competence.  This study set out to investigate undergraduates’ perceptions on the integration of a digital course offering workplace English to be used along with the existing curriculum at the University of Technology and applied Sciences (UTAS) in Nizwa. The proposed course will be developed in line with the results of the study and the literature review. A questionnaire survey used to gain insights from over 200 undergraduates at the UTAS. Findings of the study revealed that most of the participants were in favour of the idea of integrating the proposed course. The study provided a set of implications and recommendations that are of significant value for stakeholders and course designers in educational institutions and industrial sectors.